Identification of the Receptor-Binding Protein in 936-Species Lactococcal Bacteriophages - Dupont, Kitt (American Society for Microbiology, 2004)
The aim of this work was to identify genes responsible for host recognition in the lactococcal phages sk1 and bIL170 belonging to species 936. These phages have a high level of DNA identity but different host ranges. Bioinformatic analysis indicated that homologous genes, orf18 in sk1 and orf20 in bIL170, could be the receptor-binding protein (RBP) genes, since the resulting proteins were unrelated in the C-terminal part and showed homology to different groups of proteins hypothetically involved in host recognition. Consequently, chimeric bIL170 phages carrying orf18 from sk1 were generated. The recombinant phages were able to form plaques on the sk1 host Lactococcus lactis MG1614, and recombination was verified by PCR analysis directly with the plaques. A polyclonal antiserum raised against the C-terminal part of phage sk1 ORF18 was used in immunogold electron microscopy to demonstrate that ORF18 is located at the tip of the tail. Sequence analysis of corresponding proteins from other lactococcal phages belonging to species 936 showed that the N-terminal parts of the RBPs were very similar, while the C-terminal parts varied, suggesting that the C-terminal part plays a role in receptor binding. The phages investigated could be grouped into sk1-like phages (p2, fd13, jj50, and φ7) and bIL170-like phages (P008, P113G, P272, and bIL66) on the basis of the homology of their RBPs to the C-terminal part of ORF18 in sk1 and ORF20 in bIL170, respectively. Interestingly, sk1-like phages bind to and infect a defined group of L. lactis subsp. cremoris strains, while bIL170-like phages bind to and infect a defined group of L. lactis subsp. lactis strains.